Scaffolding students in evaluating the credibility of evidence using a reflective web-based inquiry environment on Biotechnology - Kafouris, Dimitris; Iolie Nicolaidou; Terzian, Frederiki; Hadjichambis, Andreas Ch.; Kyza, Eleni A. (My University, 2010)
This case study investigated scaffolding to support twelve 11th grade students' collaborative construction of evidence-based explanations and their evaluation of the credibility of evidence through the utilization of a web-based reflective inquiry environment on Biotechnology. Over eleven 90-minute lessons students investigated and evaluated scientific data relating to the cultivation of genetically modified plants. The analysis of pre-and post-tests on students' conceptual understanding of Biotechnology topics and their skills in evaluating the credibility of evidence revealed learning gains and suggested that the intervention was successful. Students' written explanations in task-related artifacts and the analysis of two groups' videotaped discussions showed that the students became sensitive to credibility criteria, questioned the sources of data and correctly identified sources of low and high credibility. Students' difficulty in applying methodological criteria suggests that this criterion should be addressed in future studies.
Keywords: Students; Collaborative construction; Conceptual understanding; Evidence-based; Learning gain; Scientific data; Biotechnology; Scaffolds; Video recording; Websites